2010
DOI: 10.1007/s11816-009-0121-8
|View full text |Cite
|
Sign up to set email alerts
|

Growth, secondary metabolite production and antioxidant enzyme response of Morinda citrifolia adventitious root as affected by auxin and cytokinin

Abstract: Morinda citrifolia adventitious roots were cultured in shake flasks using Murashige and Skoog medium with different types and concentrations of auxin and cytokinin. Root (fresh weight and dry weight) accumulation was enhanced at 5 mg l -1 indole butyric acid (IBA) and at 7 and 9 mg l -1 naphthalene acetic acid (NAA). On the other hand, 9 mg l -1 NAA decreased the anthraquinone, phenolic and flavonoid contents more severely than 9 mg l -1 IBA. When adventitious roots were treated with kinetin (0.1, 0.3 and 0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…In C. lanceolata, IBA positively affected the growth of roots and lancemaside A accumulation in the transgenic hairy roots. These results support the idea that IBA, a phytohormone, could affect secondary metabolism, particularly of triterpenoid compounds produced from various medicinal plants (Kim et al 2003;Baque et al 2010). …”
Section: Induction Of Hairy Rootssupporting
confidence: 84%
“…In C. lanceolata, IBA positively affected the growth of roots and lancemaside A accumulation in the transgenic hairy roots. These results support the idea that IBA, a phytohormone, could affect secondary metabolism, particularly of triterpenoid compounds produced from various medicinal plants (Kim et al 2003;Baque et al 2010). …”
Section: Induction Of Hairy Rootssupporting
confidence: 84%
“…Similarly, several workers have also used the liquid medium to establish the hairy root growth (He-Ping et al 2011;Pavlov et al 2005;Romero et al 2009;Sivanesan and Ryong Jeong 2009). Few previous studies support this idea that IBA could positively affect growth and secondary metabolism of various medicinal plants (Kim et al 2003;Baque et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…There are several lines of evidence suggesting that exogenous auxin increase enzyme activity during rooting or in tissue culture. It has also been demonstrated that exogenous auxin added to MS medium increased the antioxidant enzyme such as peroxidase and catalase (Tyburski et al 2009;Baque et al 2010). Auxin synthesis in the transformed hairy roots and also increasing its content in MS medium might be a signal for increased activity of antioxidant enzymes in the transformed roots.…”
Section: Discussionmentioning
confidence: 97%